Analisis Pengendalian Kualitas Produk PC Slab Tipe A untuk Meminimalkan Defect Menggunakan RCA dan FMEA di PT.XYZ - Galih Putri Pramesti; Pandena Kicky Basuki Putri; Hady Sofyan (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
The success of a production process is highly dependent on effective quality control. In this study, the focus is directed toward Pc Slab Type A products manufactured by PT. XYZ, a precast concrete company for highways and building structures. The evaluation emphasizes efforts to reduce chipping defects. Improvement priorities were determined using the Failure Mode and Effect Analysis (FMEA) method based on the Risk Priority Number (RPN). Root Cause Analysis (RCA) was applied to identify the underlying problems. The analysis revealed that the dominant factor comes from the human aspect, with the highest RPN value of 294, namely the lack of regular supervision. Additional contributing factors include improper mold opening methods (RPN 216), inconsistent worker performance (RPN 175), inter-division transfers (RPN 125), and delayed maintenance schedules (RPN 120). All causes were elaborated using the 5W+1H approach, covering reasons, locations, timing, implementation, and proposed corrective actions.